PENGARUH EKSTRAK DAUN SIRIH (Pipper Betle.L) SEBAGAI PERENDAM TELUR AYAM RAS KONSUMSI TERHADAP DAYA AWET PADA PENYIMPANAN SUHU RUANG - Eka Wulandari; Obin Rachmawan; Ahmad Tafik Taofik; Nono Suwarno; Ahmad Faisal (JURNAL ISTEK, 2013)
This research was conducted in Laboratory of Processing Livestock Product Technology at Faculty of Animal Husbandry, Padjadjaran University, Sumedang from July 31thto September 3th, 2010. The aim of this research was to find out the level of concentration of betle leaf extract as an hen’s egg soaker produce thes longest shelf life terms of haugh unit value, albumen index, and yolk index. This research used an experimental method with a Clompetely Randomized Design. There were five kinds treatments concentration level of betle leaf extract (P1=0%, P2=15%, P3=30%, P4=45%, P5=60%) with four replications. Duncan multiple range test were held to find the difference between any treatment in this research. The result of the research shows the use of betle leaf with the concentration level of 60% produce the longest shelf life 34 days in term haugh unit value, 32,75 days in terms of albumen index value and 34 days in term of yolk index value.